Luteal activity and effect of dietary energy restriction on follicular development in lactating cows. (4th April 2017) - Comin, A; Peric, T; Montillo, M; Cappa, A; Marchi, V; Veronesi, MC; Prandi, A
Contents: The aim of this research has been to evaluate the presence of anomalies in the ovarian cycle activity during postpartum and to verify whether 72‐hr dietary fasting during the dominance phase, the phase before ovulation, might modify the ovarian follicle population. The presence of anomalies in ovarian cycle activity has been evaluated in 30 Italian Friesian cows starting from 20 days postpartum until 211 days of lactation. Long oestrus and brief dioestrus or scarce luteal activity have been the main anomalies found through measuring progesterone concentrations in the whey. Until 100 days of lactation, the BCS values of the problematic animals have been significantly lower than those in animals with normal ovarian activity. After 100 days of lactation, the ovarian anomalies continued to appear despite the fact that all the animals have reached comparable BCS values. Starting from the results of this trial, the effect of 72‐hr dietary fasting on dominant follicles has been studied in six cows. Ultrasonography revealed that the diameter of the follicles at 71 days postpartum has been significantly lower than at 181 days. A 72‐hr dietary restriction at 101 and 211 days postpartum did not affect the size of the dominant follicle. However, at 101 days postpartum, half of the animals presented follicular cysts. The effect of fasting differed if the animal has been in early postpartum or 211 days of lactation. Further researches are necessary to understand how different metabolic conditions can modify the follicular population but on the other hand the study shows the utility for farmers and field veterinarians of monitoring the resumption of the ovarian cycle postpartum through the whey progesterone concentrations.